The Effects of Two Different Intensities of Concurrent Training on Pulmonary Function in Female Patients With Type II Diabetes - Amirhossein Haghighi; Malihe Ebrahimi; Roya Askari; Gholamreza Nouri; Mitra khademosharie (Physical Treatments, 2025)
Purpose: Type 2 diabetes is associated with reduced lung function. The purpose of this study was to investigate the effects of two different intensities of concurrent training on pulmonary function in female patients with type II diabetes. Methods: 24 women with type 2 diabetes were recruited as volunteers and randomly assigned to one of three following groups: High intensity (A), moderate intensity (B), and a control group (C). The training program included 12 weeks of concurrent exercise training (resistance and aerobic) at high intensity (resistance at 75-85% of 1-RM and aerobic at 70-85% of maximum heart rate) and moderate intensity (resistance at 50-75% of 1-RM and aerobic at 70-50% of maximum heart rate). The training was held in three nonconsecutive sessions per week, lasting 55-70 minutes each. Before and after the 12 weeks of training, blood samples, spirometric tests, respiratory muscle strength assessments, and upper body strength measurements were taken from all subjects. Results: The results from the pre- and post-tests in subjects showed a significant interaction effect (P<0.05) on FEF25, FEF50, FEF2575, FEV1/FVC, HbA1C, and % fat. For other parameters, there was no significant interaction effect. Conclusion: The results indicated that only respiratory and physiological parameters improved as a result of concurrent exercises with different intensities, and both types of exercise programs can be beneficial for some indicators in female patients with type 2 diabetes.